Strategic Management of Zakat Funds for Educational Initiatives: A Study at Amil Zakat Agency of Nurul Hayat - Tulab, Tali; Yurista, Dina Yustisi; Rozihan, Rozihan (Universitas Islam Sultan Agung, 2024)
The Zakat, Infaq, and Sedekah (ZIS) funds hold significant potential in Indonesia for enhancing societal welfare, especially in the educational sector. However, the optimal utilization of these funds remains a challenge, with ensuring appropriate and effective usage being the primary concern. Therefore, conducting an in-depth study on the management of ZIS fund utilization in educational programs at the Amil Zakat Institution (LAZ) Nurul Hayat becomes essential to assess its professionalism in managing and distributing funds entrusted by donors. This research adopts a qualitative approach, focusing on LAZ Nurul Hayat in Semarang. Data collection methods involve interviews with LAZ Nurul Hayat officials and documentation based on relevant articles, journals, and research. Data processing encompasses editing, classification, data analysis, and conclusion stages. The findings reveal that LAZ Nurul Hayat has successfully implemented the management of zakat fund utilization, incorporating planning, implementation, monitoring, and evaluation in the educational sector.